Nuts, anchor, self-locking, fixed, single lug, reduced series, with counterbore, with MJ threads, classifications: 1100 MPa (at ambient temperatures)/235°C, 1100 MPa (at ambient temperature)/315°C, 1100 MPa (at ambient temperature)/425°C. Dimensions. (15th March 1999) - British Standards Institution,
No abstract available